2014
DOI: 10.1371/journal.pone.0111364
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Serum Proteomic Biomarkers for Clear Cell Renal Cell Carcinoma

Abstract: ObjectiveTo investigate discriminating protein patterns and serum biomarkers between clear cell renal cell carcinoma (ccRCC) patients and healthy controls, as well as between paired pre- and post-operative ccRCC patients.MethodsWe used magnetic bead-based separation followed by matrix-assisted laser desorption ionization (MALDI) time-of-flight (TOF) mass spectrometry (MS) to identify patients with ccRCC. A total of 162 serum samples were analyzed in this study, among which there were 58 serum samples from ccRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…ZFP3 contains a conserved structural motif that mediates its binding to protein, DNA and RNA, in humans ZFP3 has been localized to chromosome 17p12-17pter [46]. Ming et al reported that the ZFP3 had protective effect in clear cell renal cell carcinoma [47], which was consistent with our research.…”
Section: Discussionsupporting
confidence: 92%
“…ZFP3 contains a conserved structural motif that mediates its binding to protein, DNA and RNA, in humans ZFP3 has been localized to chromosome 17p12-17pter [46]. Ming et al reported that the ZFP3 had protective effect in clear cell renal cell carcinoma [47], which was consistent with our research.…”
Section: Discussionsupporting
confidence: 92%
“…Mammography is one of the most important screening tools as a population strategy, but has limitations in young women (under 40 years old) or women with large breasts, with a sensitivity of as low as 25–59% and high rates of false negative and false positive in diagnosis [ 170 ]. Blood-based proteomics as a screening diagnostic with novel noninvasive biomarkers for the early detection of BCa in asymptomatic individuals for the diagnosis and prognosis of the disease states has been an area of research interest [ 171 , 172 ]. Promising candidate biomarkers such as CA125, carcinoembryonic antigen (CEA), oncogenic protein RS/DJ-1, human epidermal growth factor receptor-2 (HER2), and circulating cytokeratin fragments (tissue polypeptide antigen (TPA), tissue polypeptide-specific antigen (TPS), and CYFRA 21-1) have been identified, but are pending validation [ 173 ].…”
Section: Clinical Serum/plasma Proteomics and Molecular Signaturesmentioning
confidence: 99%
“…When we used ClinProtools Software (Bruker Daltonics) to search for differential proteins and design models,[ 10 ] we found that not only the number, mass of candidate proteins, but also the potential importance of these proteins; that is, candidate proteins with lower peak intensities appeared to be less meaningful in this context. We, therefore, tried to improve the analytic process.…”
Section: Ethodsmentioning
confidence: 99%